In women with gestational diabetes mellitus factors influencing growth have a larger effect on placental weight than on birth weight. (July 2016) - Ramos, A.; Caimari, F.; Pujol, I.M.; García-Patterson, A.; Ginovart, G.; Adelantado, J.M.; Corcoy, R.
Abstract: Background and aims: Excessive fetal and placental growth are very common in diabetic pregnancy. We aimed to analyze in women with gestational diabetes mellitus (GDM) the association with birth weight (BW), placental weight (PW) and placental-to-birth weight (PWBW) ratio of acknowledged BW predictors. Material and methods: We performed a retrospective analysis of a prospective cohort database from a tertiary hospital. Inclusion criteria were singleton pregnancy, diagnosis of GDM, delivery between 1982 and 2011 and gestational age at birth ≥23 weeks. Multiple regression analysis was performed using as dependent variables BW, PW and PWBW ratio and as independent ones maternal characteristics at baseline, metabolic characteristics (GDM diagnosis, treatment, control), pregnancy-induced hypertension, gestational age at delivery and fetal sex. Two sensitivity analyses were performed. Results: We evaluated 2547 women, PW being available in 85.3%. BW was 3260 g (2976, 3575), PW 620 g (540, 720) and PWBW ratio 19.27 (17.20, 21.47). Among the 24 analyzed variables, there was an important overlap among those associated with BW, PW and PWBW ratio. For most characteristics associated with both BW and PW, the magnitude of the association was greater for the latter, both when promoting growth (i.e. prepregnancy body mass index, 3 h plasma glucose at diagnosis) and when restricting it (insulin treatment). Conclusion: We conclude that in women with GDM and singleton pregnancies, variables associated with BW, PW and PWBW ratio overlap. The latter is the result of disproportionate associations with BW and PW, usually larger with PW.